Innovation of Spice Chocolate and Chocolate Derivatives as an Effort to Realize Self-reliance in Bodag Village - Rizka Mulyani; Prakoso Adi; Dea Yoana Putri Damayanti; Dewi Irawati; Arum Puspa Maharani; Citra Bherly Fantika Wibowo; Ragil Siwi Puspa Khirana; Anisa Kurniawati; Bowis Fatwa Afif; Ceut Halimah Heca Wardani; Cindy Amelia; Hanifah Eka Cahyani; Amiwiti Fayyadh Islami Falih; Earlian Zaka Bintang Lazuardi (LPPM Universitas Muhammadiyah Tasikmalaya, 2023)
Cocoa is one of the biggest commodities in Madiun Regency. Cocoa has the potential to be developed into processed chocolate products that will become peculiar souvenirs of Madiun Regency. This potential has been utilized by the Village-Owned Enterprises (BUMDes) of Rumah Coklat Bodag, Bodag Village, Kare District, Madiun Regency. However, the lack of chocolate product innovation and the underutlillization of cocoa fat is still faced by this Village-Owned-Enterprises. The main purpose of this empowermwnt activity is to empower this BUMDes to innovate chocolate products and their derivatives, especially in utilizing the potential of spices and cocoa fat. In this empowerment activity, training and mentoring of chocolate production with the addition of spices (ginger, cardamom, and cloves), and training on making soap made from cocoa fat have been carried out. This training and mentoring has succeeded in creating innovative chocolate spices and soaps made from cocoa butter. These products can later can be a peculiar product of Madiun Regency. In addition, through this activity, counseling on food safety has also been carried out to increase the knowledge of the residents of Bodag village, so that the products produced by Bodag village have good quality. Based on observations made by the team, there was an increase in the knowledge of Bodag villagers regarding food safety after the counseling. This indicates that the transfer of knowledge regarding food safety has been successfully carried out by the team to the residents of Bodag village.